EVIDENCE FOR ASYMMETRIC NONVOLCANIC RIFTING AND SLOW INCIPIENT OCEANIC ACCRETION FROM SEISMIC REFLECTION DATA OF THE NEWFOUDLAND MARGIN - Shillington D.J.; Holbrook W.S.; Van Avendonk H.J.A.; Tucholke B.E.; Hopper J.R.; Louden K.E.; Larsen H.C.; Nunes G.T. (My University, 2006)
Prestack depth migrations of seismic reflection data collected around the Ocean Drilling Program (ODP) Leg 210 transect on the Newfoundland nonvolcanic margin delineate three domains: (1) extended continental crust, (2) transitional basement, and (3) apparent slow spreading oceanic basement beyond anomaly M3 and indicate first-order differences between this margin and its well-studied conjugate, the Iberia margin. Extended continental crust thins abruptly with few observed faults, in stark contrast with the system of seaward dipping normal faults and detachments imaged within continental crust off Iberia. Transition zone basement typically appears featureless in seismic reflection profiles, but where its character can be discerned, it does not resemble most images of exhumed peridotite off Iberia. Seismic observations allow three explanations for transitional basement: (1) slow spreading oceanic basement produced by unstable early seafloor spreading, (2) exhumed, serpentinized mantle with different properties from that off Iberia, and (3) thinned continental crust, likely emplaced by one or more detachment or rolling-hinge faults. Although we cannot definitively discriminate between these possibilities, seismic reflection profiles together with coincident wide-angle seismic refraction data tentatively suggest that the majority of transitional basement is thinned continental crust emplaced during the late stages of rifting. Finally, seismic profiles image abundant faults and significant basement topography in apparent oceanic basement. These observations, together with magnetic anomaly interpretations and the recovery of mantle peridotites at ODP Site 1277, appear to be best explained by the interplay of extension and magmatism during the transition from non-volcanic rifting to a slow spreading oceanic accretion system. Copyright 2006 by the American Geophysical Union.